BIOPOLÍTICA E RESISTÊNCIA EM MICHEL FOUCAULT - SILVA, Antonio José Carlos da (2023)
This Dissertation has in its central scope the understanding of the concept of biopolitics and resistance in the thought of Michel Foucault. The central questions that guide our concerns are: how is understood the biopolitics of Foucault in view of the complexity of power relations? If resistance makes us change routes, deviate from paths, reflect deeply, abandon habits, customs, behaviors, change statutes and enable new perspectives to live in society more harmoniously and fairly, Why do people today not revolt with so many problems made possible by the State, injustices with the most needy, naturalness of corruption, disregard for environmental policies, racism and death? What is the meaning of resistance in the thought of Michel Foucault? In chapter one, we will investigate the notion of biopolitics, as a conductor of conduct, from the perspective of Social Medicine, of sovereignty, finally, as governmentality. Chapter two, we will try to analyze power, resistance and revolt, as a correlate of biopolitical action, considering that in the agonistic field, space of freedom practices, of politics about life, life has the possibility of saying no to such attempt at circumscription, domination, subjectivation. Finally, in the third chapter, we will seek to understand the counter-conduct and freedom in the biopolitical field, as integral, necessary and permanent actions as an essential and vital condition in the present time of political rationalities, of governmentality. It is understood that these actions are manifestations of practices of freedoms in the wake of the ethical-political, allowing the field of strategic situations to remain open through an aesthetic of existence. In this glimpse, the practices of freedom are essential for such an aesthetic of life. It is concluded that it is in this practical field correlated with social tensions, confrontations, arrests, demonstrations, deaths, that Foucault dives deep, seeing in strategic situations the weaknesses of truth games and how new relationships, new objects, new subjects are constituted, new morality, in short, a new mode of conduct, with regard to the technologies of biopolitical power.